Analisis Kinerja Pegawai Melalui Pengaruh Mutasi dan Budaya Organisasi pada Dinas Lingkungan Hidup Kota Solok - Winda Safitri (Universitas Putra Indonesia YPTK Padang, 2022)
This study uses a survey approach, namely the method of collecting data using primary data. Primary data was obtained by distributing questionnaires to 71 respondents. The analytical method used is the multiple regression method. The results of the regression analysis in this study indicate that: There is a positive and significant relationship between job mutations, there is a positive and significant relationship between organizational culture and employees, there is a positive but not significant relationship between performance mutations and employees, there is a positive and significant relationship between organizational culture and organizational culture. on employee performance, there is a positive and significant influence between employee performance, organizational culture is not mediated by work objectives on employee performance. The coefficient of determination of the variable is a value of 0.591, meaning that mutations and organizational culture affect the variables by 59.1%, and the remaining 40.9% is not influenced by other variables that are not included in the research model.